Implications of Developing Deep-Sea Arctic Fisheries for Greenland Halibut (Reinhardtius hippoglossoides): Inshore Stock Connectivity and Capture Induced Stress of Ecologically Important Fish Species - Barkley, Amanda Noel (University of Windsor, 2015)
One of the most pressing issues facing developing Arctic fisheries is a lack of scientific knowledge available to inform management. This thesis develops two key ideas essential to establishing a sustainable harvest of Greenland Halibut (Reinhardtius hippoglossoides) within Scott Inlet, Baffin Island: inshore/offshore connectivity of Greenland Halibut stocks, and capture induced stress of Greenland Halibut and Greenland Shark (Somniosus microcephalus). The majority of Greenland Halibut only utilised the inshore environment during the summer, ice-free, season spending about 27±14 days within the system before exiting offshore. A small resident portion of fish, spent on average 261±79 days within Scott Inlet throughout the year. Capture stress indicated that undersized Greenland Halibut do not express greater physiological perturbations, yet Greenland Sharks captured at greater depths had higher lactate values (300-600 m: 1.6±0.5 mmol/L and 700-900 m: 3.7±1.2 mmol/L). This information will contribute to the sustainable development of Greenland Halibut fisheries in the Arctic.